Why Generative Anthropology? In defense of speculative thinking - Gans, Eric Lawrence (2023)
In my work in generative anthropology (GA) over the decades, I have emphasized the necessity of referring to the originary hypothesis as providing a model for the basic forms of human culture. I am quite aware that GA cannot be a rigorous, let alone an axiomatic system, but the principle that has dictated this effort...